Bitcoin investment during Covid-19: the critical factors influencing its adoption - Abubakar, Adamu; Al-Hussaini, AbulFathi Ibrahim Saleh (Global Academic Excellence (M) Sdn Bhd, 2022)
Bitcoin was the first virtual currency to be created in 2009 as a decentralized digital currency that could be transferred from one user to another over the peer-to-peer bitcoin network without the use of intermediaries such as banks and other financial institutions. In terms of finance, governments and other experts are concerned that Bitcoin can be used to avoid currency restrictions, for money manipulation, or criminal activities, and that it may be risky for investors due to the absence of regulations. The purpose of this study is to investigate the factors influencing Bitcoin investment adoption in Covid-19, examine the mediating factors influencing Bitcoin investment adoption in Covid-19, and propose a model of influencing Bitcoin investment adoption in Covid-19. Therefore, a methodological method was employed to accomplish these aims. The theory adopted is the theory of planned behaviour. Purposive sampling was used as the sampling method for the study. A total of 101 full responses were obtained to the web-based questionnaire. Partial Least Squares Structural Equation Modeling (PLS-SEM 3) is utilized to analyze the study's findings. Perceived Behavior Control and Perceived Lack of Alternatives were found to have a favourable association with Intention to Invest in Bitcoin. Meanwhile, Perceived External Pressure has the reverse result, having a marginal influence on the Decision to Invest in Bitcoin. Surprisingly, Perceived Lack of Alternative completely mediates the interaction between Perceived External Pressure and Desire to Invest in Bitcoin. It is anticipated that this analysis would have a clearer picture of Investors' and Consumers' Action on Investing in Bitcoin During Covid-19.